2021
DOI: 10.1111/iju.14686
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the objective response to and number of cycles of platinum‐based first‐line chemotherapy for metastatic urothelial carcinoma on overall survival of patients treated with pembrolizumab

Abstract: To investigate the impact of the number of cycles and objective response to chemotherapy on overall survival in patients with metastatic urothelial carcinoma treated with pembrolizumab. Methods: This multicenter, retrospective study included 755 patients from 59 institutions with advanced, chemoresistant urothelial carcinoma who received pembrolizumab. The associations of the overall survival with the number of cycles and best objective response were investigated using Cox multiple regression analysis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Our data showed that the overall response rate to subsequent chemotherapy after pembrolizumab failure was 20.9%, which is comparable to previous results in similar settings 7,8 . This is also consistent with expected results from patients who previously failed chemotherapy without previous ICI exposure, 9,10 suggesting that chemotherapy responses are maintained irrespective of previous exposure to ICIs. Of the 115 patients with subsequent chemotherapy, four had CR to chemotherapy, all of which were rechallenged cases of gemcitabine and cisplatin chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that the overall response rate to subsequent chemotherapy after pembrolizumab failure was 20.9%, which is comparable to previous results in similar settings 7,8 . This is also consistent with expected results from patients who previously failed chemotherapy without previous ICI exposure, 9,10 suggesting that chemotherapy responses are maintained irrespective of previous exposure to ICIs. Of the 115 patients with subsequent chemotherapy, four had CR to chemotherapy, all of which were rechallenged cases of gemcitabine and cisplatin chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Most previous studies have analyzed and reported survival rates from the date of ICI initiation. [2][3][4][5][6]16 The pivotal trial, KEYNOTE-045, reported that median OS in the pembrolizumab group was 10.3 months as compared to 7.4 months in the chemotherapy group (P = 0.002), resulting in a 2.9-month survival benefit from the initiation of pembrolizumab or investigator's choice of chemotherapy. A recent report from the Japan Urological Oncology Group demonstrated a positive correlation between response to pembrolizumab and response to chemotherapy, 16 implying that time-totreatment failure of first-line chemotherapy is closely associated with that of second-line ICI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6]16 The pivotal trial, KEYNOTE-045, reported that median OS in the pembrolizumab group was 10.3 months as compared to 7.4 months in the chemotherapy group (P = 0.002), resulting in a 2.9-month survival benefit from the initiation of pembrolizumab or investigator's choice of chemotherapy. A recent report from the Japan Urological Oncology Group demonstrated a positive correlation between response to pembrolizumab and response to chemotherapy, 16 implying that time-totreatment failure of first-line chemotherapy is closely associated with that of second-line ICI therapy. Therefore, to discuss the real survival benefit from the advent of ICI, we need to evaluate survival from the initiation of first-line chemotherapy, not from the initiation of second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 Systemic chemotherapy and ICIs are two immunoregulation agents frequently administered to patients with advanced UC. 7 , 8 , 9 , 10 , 11 , 12 Treatment with ICIs in combination or ICIs plus TKIs is considered the standard of care for patients with metastatic RCC. 13 , 14 , 15 , 16 , 17 , 18 Furthermore, immune‐related AEs are closely associated with high‐dose steroid administration in patients treated with ICIs, and steroid use has been associated with impaired humoral response to SARS‐CoV‐2 mRNA vaccines in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%